A new three party key establishment scheme: Applicable for internet-enabled sensor networks. (May 2015) - Nasiraee, Hassan; Mohasefi, Jamshid B.
Abstract: Internet-Enabled Sensor Networks (IESNs) play an important role in Internet-of-Things (IoT) which usually need key establishment and secure communication. In this paper, first we show why existing three party key establishment schemes cannot be easily applied to IESN. Second we propose an extension of traditional three-party key establishment schemes (such as SNEP, BBF and OR). The method provides DoS and Sybil attack resistance and benefits from low communication cost, independence of prior sensor deployment knowledge and support for node mobility. The extension is simple in the sense that an interested node that joins the network is responsible to aggregate neighbors' information and to send a request to the trusted party to get required keys. Our proposal reduces energy consumption about 75% vs. SNEP, 50% vs. BBF and 78% vs. OR, as three well-known previous schemes, which causes a significant increase in lifetime of nodes.